Metacognition Analysis in Problem Solving of Field Independent and Field Dependent Students - Maria Ronauli Sihotang; Nizlel Huda; Novferma (Riemann: Research of Mathematics and Mathematics Education, 2024)
This study aims to describe students' metacognition in solving PtLSV problems regarding field-independent and field-dependent cognitive styles. This research was conducted at SMP Negeri 1 Muaro Jambi in the 2023/2024 academic year. This type of research is qualitative research. The subjects of this study were 4 students of class VIIA of SMP Negeri 1 Muaro Jambi, 2 students each with field-independent cognitive style and field-dependent cognitive style. Data collection methods were the results of the GEFT test to determine students with field-independent and field-dependent cognitive styles , PtLSV problem-solving questions, unstructured interviews and documentation. Data analysis techniques consisted of data collection, data reduction, data presentation and conclusion. The results showed that students with field-independent cognitive style met all indicators of metacognitive activity in problem-solving. However, students with field-dependent cognitive style did not meet the metacognitive evaluation indicators in re-checking the results, and errors were seen in operating PtLSV problem-solving. The second student with a field-dependent cognitive style, he only met the metacognitive activity indicators in understanding problems but did not yet have a strategy in solving PtLSV problem-solving questions.